Kesedaran membayar zakat: Apakah faktor penentunya? - Wahid, Hairunnizam; Mohd Noor, Mohd Ali; Ahmad, Sanep (Universiti Utara Malaysia, 2005)
The awareness of the responsibility to pay (zakat) on property is still perceived to be very low among the zakat payers. This is perhaps due to the misunderstanding of the Muslim masses that the only responsibility to pay zakat is (fitrah) in the month of Ramadan. In this case the role of Islamic teaching plays a pivotal role in educating the Muslim through a law that enforces payment and the integrity of the zakat Institution. Because of the stated weaknesses, there exist certain individuals that have no legitimate reasons not to pay zakat, while some pay to unauthorised individuals or organizations. This problem of zakat evasion also represents the stealing of the wealth of others that lies in our property. Thus, this study aims to identify significant factors that contribute toward the payment of zakat relating to location, demographic, facility and educational factors. A logistic regression model was used to identify the variables. Results of the econometric analysis showed that payer satisfaction of zakat distribution is one of the significant factors and several suggestions are given to improve the awareness among the payers.